Evaluating the impact of a national naloxone programme on ambulance attendance at overdose incidents: a controlled time–series analysis. (6th November 2016) - McAuley, Andrew; Bouttell, Janet; Barnsdale, Lee; Mackay, Daniel; Lewsey, Jim; Hunter, Carole; Robinson, Mark
Abstract: Background and Aims: It has been suggested that distributing naloxone to people who inject drugs (PWID) will lead to fewer attendances by emergency medical services at opioid‐related overdose incidents if peer administration of naloxone was perceived to have resuscitated the overdose victim successfully. This study evaluated the impact of a national naloxone programme (NNP) on ambulance attendance at opioid‐related overdose incidents throughout Scotland. Specifically, we aimed to answer the following research questions: is there evidence of an association between ambulance call‐outs to opioid‐related overdose incidents and the cumulative number of 'take‐home naloxone' (THN) kits in issue; and is there evidence of an association between ambulance call‐outs to opioid‐related overdose incidents in early adopter (pilot) or later adopting (non‐pilot) regions and the cumulative number of THN kits issued in those areas? Design: Controlled time–series analysis. Setting: Scotland, UK, 2008–15. Participants: Pre‐NNP implementation period for the evaluation was defined as 1 April 2008 to 31 March 2011 and the post‐implementation period as 1 April 2011 to 31 March 2015. In total, 3721 ambulance attendances at opioid‐related overdose were recorded for the pre‐NNP implementation period across 158 weeks (mean 23.6 attendances per week) and 5258 attendances across 212 weeks in the post‐implementation period (mean 24.8 attendances per week). Intervention: Scotland's NNP; formally implemented on 1 April 2011. Measurements: Primary outcome measure was weekly incidence (counts) of call‐outs to opioid‐related overdoses at national and regional Health Board level. Data were acquired from the Scottish Ambulance Service (SAS). Models were adjusted for opioid replacement therapy using data acquired from the Information Services Division on monthly sums of all dispensed methadone and buprenorphine in the study period. Models were adjusted further for a control group: weekly incidence (counts) of call‐outs to heroin‐related overdose in the London Borough area acquired from the London Ambulance Service. Findings: There was no significant association between SAS call‐outs to opioid‐related overdose incidents and THN kits in issue for Scotland as a whole (coefficient 0.009, 95% confidence intervals = −0.01, 0.03, P = 0.39). In addition, the magnitude of association between THN kits and SAS call‐outs did not differ significantly between pilot and non‐pilot regions (interaction test, P = 0.62). Conclusions: The supply of take‐home naloxone kits through a National Naloxone Programme in Scotland was not associated clearly with a decrease in ambulance attendance at opioid‐related overdose incidents in the 4‐year period after it was implemented in April 2011.